(untitled) (2011)
In this study we propose a multi-source data approach for quantifying long-term flooding and aquifer recharge in ungauged ephemeral rivers. The methodology is applied to the Buffels River, at 9000 km2 the largest ephemeral river in Namaqualand (NW South Africa), a region with scarce stream flow records limiting research investigating hydrological response to global change. Daily discharge and annual flood series (1965-2006) were estimated from a distributed rainfall-runoff hydrological model (TETIS) using rainfall gauge records located within the catchment. The model was calibrated and validated with data collected during a two year monitoring programme (2005-2006) at two stream flow stations, one each in the upper and lower reaches of the catchment. In addition to the modelled flow records, non-systematic flood data were reconstructed using both sedimentary and documentary evidence. The palaeoflood record identified at least 25 large floods during the last 700 yr; with the largest floods reaching a minimum discharge of 255 m3 s-1 (450 yr return period) in the upper basin, and 510 m3 s-1 (100 yr return period) in the lower catchment. Since AD 1925, the flood hydrology of the Buffels River has been characterised by a decrease in the magnitude and frequency of extreme floods, with palaeoflood discharges (period 1500-1921) five times greater than the largest modelled floods during the period 1965-2006. Large floods generated the highest hydrograph volumes, however their contribution to aquifer recharge is limited as this depends on other factors such as flood duration and storage capacity of the unsaturated zone prior to the flood. Floods having average return intervals of 5-10 yr (120-140 m3 s-1) and flowing for 12 days are able to fully saturate the Spektakel aquifer in the lower Buffels River basin. Alluvial aquifer storage capacity limiting potential recharge by the largest floods is a common problem in arid environments, with the largest infiltration volumes favoured by increasing depth to groundwater levels. © Author(s) 2011.